2014
DOI: 10.7314/apjcp.2014.15.7.3071
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Postoperative Nosocomial Pneumonia in Stage I-IIIa Lung Cancer Patients

Abstract: Background: To investigate the related risk factors of postoperative nosocomial pneumonia (POP) in patients withⅠ-Ⅲa lung cancer. Methods: Medical records of 511 patients who underwent resection for lung cancer between January 2012 to December 2012 were retrospectively reviewed. Risk factors of postoperative pneumonia were identified and evaluated by univariate and multivariate analyses. Results: The incidence of postoperative pneumonia in these lung cancer patients was 2.9% (15 cases). Compared with 496 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 25 publications
2
30
0
1
Order By: Relevance
“…A previous study (Lee, 2008) identified the 45-64 year age bracket as the group most likely to develop VAP; a foreign report (Tablan et al, 2004) also identified infants and the elderly (≥ 65 years) as groups most vulnerable to VAP, also consistent with the results of this study, although this study included only patients greater than 18 years of age. In this study, patients aged 65 years or more were found to be have risk of VAP in 5.56 times(p=0.021), patients with lung cancer were found to be 5.81 times (Wang et al, 2014) compared to patients aged 60 years or more (p=0.018).…”
Section: Discussionmentioning
confidence: 55%
“…A previous study (Lee, 2008) identified the 45-64 year age bracket as the group most likely to develop VAP; a foreign report (Tablan et al, 2004) also identified infants and the elderly (≥ 65 years) as groups most vulnerable to VAP, also consistent with the results of this study, although this study included only patients greater than 18 years of age. In this study, patients aged 65 years or more were found to be have risk of VAP in 5.56 times(p=0.021), patients with lung cancer were found to be 5.81 times (Wang et al, 2014) compared to patients aged 60 years or more (p=0.018).…”
Section: Discussionmentioning
confidence: 55%
“…A retrospective study by Simonsen et al [44] looked at 7479 lung cancer surgery patients, finding 3.6% of them developed pneumonia postoperatively. Similarly, a retrospective study by Wang et al [45] studied 511 patients who underwent lung resection for cancer. They found 2.9% of patients developed postoperative pneumonia.…”
Section: Resultsmentioning
confidence: 99%
“…Patients who underwent open thoracotomy had the highest risk of postoperative pneumonia (aOR: 1.79; 95% CI: 1.02 - 3.17). Wang et al [45] found age > 60 years was a significant independent risk factor (OR: 5.813; P = 0.018), as was squamous cell carcinoma histopathology (OR: 5.831; P < 0.001). Preoperative COPD (OR: 0.031; 95% CI: 0.012 - 0.078; P < 0.001) and WBC count (OR: 1.451; 95% CI: 1.212 - 1.736; P < 0.001) were identified as independent risk factors by Lai et al [47].…”
Section: Resultsmentioning
confidence: 99%
“…Actually, there are limited data on the incidence of postoperative pneumonia (POP) following major cancer surgery. The incidence of POP after lung cancer surgery ranged from 2.1% to 10.7% [4][5][6][7][8][9][10][11], after gastric cancer surgery 3.6% to 4.3% [12,13], and after colorectal cancer surgery 6.2% [14]. To our knowledge, however, there have been few studies conducted on the incidence of POP after surgery in other cancers or comparative analyses of the incidence of various cancer types.…”
Section: Introductionmentioning
confidence: 99%